2001
DOI: 10.1046/j.0953-816x.2001.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Kindling of claustrum and insular cortex: comparison to perirhinal cortex in the rat

Abstract: The perirhinal cortex has recently been implicated in the kindling of limbic generalized seizures. The following experiments in rats tested the selectivity of the perirhinal cortex's epileptogenic properties by comparing its kindling profile with those of the adjacent insular cortex, posterior (dorsolateral) claustrum and amygdala. The first experiment examined the kindling and EEG profiles, and found that both the claustrum and insular cortex demonstrated rapid epileptogenic properties similar to the perirhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Given these trends, the PC has been proposed to be part of a pathway that amplifies and rapidly propagates seizure activity to motor and 13 cortical areas, giving rise to secondary generalized convulsive seizures (Kelly and Mclntyre, 1996;Mclntyre and Kelly, 2000). Interestingly, studies that compared kindling rates among the PC and the IC demonstrated similar kindling profiles (Kodama et aL, 2001;Mohapel et aL, 2001) implying that the IC may also be hyperexcitable and important in producing kindled seizures.…”
Section: Extrahippocampal Involvement In Tle: the Perirhinal Cortexmentioning
confidence: 96%
See 2 more Smart Citations
“…Given these trends, the PC has been proposed to be part of a pathway that amplifies and rapidly propagates seizure activity to motor and 13 cortical areas, giving rise to secondary generalized convulsive seizures (Kelly and Mclntyre, 1996;Mclntyre and Kelly, 2000). Interestingly, studies that compared kindling rates among the PC and the IC demonstrated similar kindling profiles (Kodama et aL, 2001;Mohapel et aL, 2001) implying that the IC may also be hyperexcitable and important in producing kindled seizures.…”
Section: Extrahippocampal Involvement In Tle: the Perirhinal Cortexmentioning
confidence: 96%
“…In addition, PC kindling produces generalized motor seizures after relatively few stimulation trials, implying that it acts as a primary route for seizure propagation from limbic to neocortical structures Kelly and Mclntyre, 1996;Sato et al, 1998;Barnes et al, 2005). Interestingly, the IC exhibits comparable kindling rates to the PC, and presents similar EEG profiles during kindled seizures (Kodama et al, 2001;Mohapel et al, 2001). Furthermore, the RAIC is a principle target for PC efferents (Delatour and Witter, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume 7,2005 in neuronal populations that are activated by seizures (Morris et al, 2000;Mohapel et al, 2001). Hippocampal-EC slices close to those studied in the IOS experiments were immunostained with two different FosB/∆FosB antibodies and analyzed 3 wk after pilocarpine (n = 28) or saline (n = 19) injection.…”
Section: Neuromolecular Medicinementioning
confidence: 99%
“…In particular, we studied hippocampal-EC slices employing intrinsic optical signal (IOS) imaging that provides information on the spatiotemporal patterns of neuronal activity (MacVicar and Hochman, 1991;Andrew et al, 1996;Jarvis et al, 1999;Weissinger et al, 2005) and thus can be used to monitor the onset and propagation of epileptiform synchronization (D'Arcangelo et al, 2001(D'Arcangelo et al, , 2005. In addition, taking advantage of FosB/∆FosB-related protein induction in neurons participating to seizures (Morris et al, 2000;Mohapel et al, 2001), we compared the in vitro findings with the ex vivo patterns of network activity identified in pilocarpine-treated epileptic rats. Both techniques provided evidence for functional downregulation of the CA3 subfield, although other hippocampal regions appeared to be hyperactive.…”
mentioning
confidence: 99%